2012
DOI: 10.3892/mmr.2012.768
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of the polyamine catabolic key enzyme SSAT prevents CDK inhibitor-induced apoptosis in Caco-2 colon cancer cells

Abstract: Roscovitine and purvalanol are purine derivative cyclin-dependent kinase (CDK) inhibitors that induce apoptosis in various types of cancer cells. However, their impact on the apoptotic cell death mechanism requires further elucidation. Natural polyamines putrescine, spermidine and spermine play essential roles in the regulation of cell growth and proliferation. Increased levels of polyamines in cells are considered to be involved in cancer progression. Intracellular polyamine levels are under the control of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…The induction of SSAT is usually accompanied by a decrease in intracellular levels of PA, in particular Spd and Spm. Our results indicated that purvalanol at 20 µM led to a decrease in total PA levels after 24 h. Recent reports suggest that many chemotherapeutic drugs such as polyamine analogues, BENSpm (Huang et al, 2005), roscovitine (Coker et al, 2012), and sulindac (Babbar et al, 2003) lead to the induction of SSAT and a lower intracellular PA pool in MCF-7 and other cancer cells.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The induction of SSAT is usually accompanied by a decrease in intracellular levels of PA, in particular Spd and Spm. Our results indicated that purvalanol at 20 µM led to a decrease in total PA levels after 24 h. Recent reports suggest that many chemotherapeutic drugs such as polyamine analogues, BENSpm (Huang et al, 2005), roscovitine (Coker et al, 2012), and sulindac (Babbar et al, 2003) lead to the induction of SSAT and a lower intracellular PA pool in MCF-7 and other cancer cells.…”
Section: Discussionsupporting
confidence: 58%
“…Previous studies reported ROS generation is linked with DNA damage and results in apoptosis (Casero et al, 2003;Arisan et al, 2012). Our previous studies showed that purvalanol and roscovitine induce ROS generation in LNCaP, DU145, PC3 prostate cancer cells, and HCT116 colon cancer cells (Arisan et al, 2012;Coker et al, 2013;. Spm co-treated cells showed a greater increase in DCFDH-DA staining than Spd co-treatment with CDK inhibitor.…”
Section: Discussionmentioning
confidence: 88%
“…In addition we determined that intracellular PA levels were decreased by EBR treatment. There are several reports showing that upregulated SSAT and PAO gene expressions caused the accumulation of high levels of ROS and apoptosis in breast and colon cancer cells lines . At this point, it should be noted that the effect of the serum amine oxidases as a possible sources of H 2 O 2 was excluded by their inhibitoramino guanidine.…”
Section: Discussionmentioning
confidence: 99%
“…For improved understanding, the control cells at all the time points have been assumed as 100% and the cell viability for tested formulations has been calculated accordingly (Coker et al, 2012;Cheah et al, 2014).…”
Section: Cell Viability Assaymentioning
confidence: 99%